Implementasi Disiplin Positif di SD/MI - Nurishlah, Laesti; Subiyono, Subiyono; Hasanah, Iis (Peneliti.net, 2022)
Learning discipline problems in Ibtidaiyah Elementary School (SD/MI) can vary depending on the context and environment of the school. This study aims to analyze the implementation of positive discipline in elementary schools / MI. The research method used is library research using a qualitative approach. The results show, Positive discipline provides significant benefits for teachers and students in elementary / MI, helping to create a conducive, motivating, and empowering learning environment for all parties involved in the learning process. By following appropriate steps and actively involving all stakeholders, schools can successfully implement positive discipline and create a conducive, motivating and supportive learning environment for all students. Through positive discipline, students learn values such as responsibility, cooperation, and integrity. This helps them become good individuals and contribute positively to society